2020
DOI: 10.1103/physrevresearch.2.022057
|View full text |Cite
|
Sign up to set email alerts
|

Energy bounds for entangled states

Abstract: We find the minimum and the maximum value for the local energy of an arbitrary finite bipartite system for any given amount of entanglement, also identifying families of states reaching these bounds and sharing formal analogies with thermal states. Then, we numerically study the probability of randomly generating pure states close to these energy bounds finding, in all the considered configurations, that it is extremely low except for the two-qubit and highly degenerate cases. These results can be important in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…In Ref. [19] we showed that, for a given degree of entanglement E, the states minimizing the average of H 0 are pure states of the form…”
Section: Minimal Background On Minimum Energy Entangled Statesmentioning
confidence: 99%
See 4 more Smart Citations

Generation of minimum energy entangled states

Piccione,
Militello,
Napoli
et al. 2020
Preprint
Self Cite
“…In Ref. [19] we showed that, for a given degree of entanglement E, the states minimizing the average of H 0 are pure states of the form…”
Section: Minimal Background On Minimum Energy Entangled Statesmentioning
confidence: 99%
“…More details about all these facts are given in Ref. [19]. The aim of this paper is to present possible strategies to generate states of the form of Eq.…”
Section: Minimal Background On Minimum Energy Entangled Statesmentioning
confidence: 99%
See 3 more Smart Citations

Generation of minimum energy entangled states

Piccione,
Militello,
Napoli
et al. 2020
Preprint
Self Cite